For a geography of human proximity - Baptista, Isabel (2005)
Based on the philosophical positions of two contemporary thinkers, Emmanuel Lévinas and Jacques Derrida, this paper intends to demonstrate the importance of a “geography of human proximity” deep-rooted in relational practices marked by the hospitality value, considered in this context as a capital competence of citizenship.